2003
DOI: 10.1063/1.1561165
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness of InGaAs/GaAs quantum dots

Abstract: The interaction between point defects in the matrix and excitons localized in self-organized InGaAs/GaAs quantum dots is investigated for structures irradiated by protons. The exciton ground state is demonstrated to be unaffected by radiation doses up to 1014 p/cm2. The close proximity of radiation-induced defects leads to a strong nonmonotonous temperature dependence of the luminescence yield: Carriers are lost via tunneling from excited quantum dot states to irradiation-induced defects below ∼100 K, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…The possibility that degradation to the TiO 2 and InP QDs materials also occurred cannot be dismissed. Based on other radiation effects studies performed on QDs, there is reported data to support the assertion that that the QDs were probably the least affected by the gamma-rays [17][18][19][20][21]. An independent study of the effects of radiation on these components would be required to differentiate the extent of degradation experience by each of the major components comprising the PPD.…”
Section: Inp Qd Ppd Aging Studies and Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The possibility that degradation to the TiO 2 and InP QDs materials also occurred cannot be dismissed. Based on other radiation effects studies performed on QDs, there is reported data to support the assertion that that the QDs were probably the least affected by the gamma-rays [17][18][19][20][21]. An independent study of the effects of radiation on these components would be required to differentiate the extent of degradation experience by each of the major components comprising the PPD.…”
Section: Inp Qd Ppd Aging Studies and Resultsmentioning
confidence: 74%
“…Inorganic QD infrared photodetectors (QDIPs) operating well into the mid infrared have attracted much attention due to the ability of varying the quantum well structure and dot size in order to change the photoluminescence spectra [16]. Enhanced radiation resistance in QD-doped InAs/GaAs lasers irradiated by various high energy ions have been reported showing that interaction of charge carriers with non-radiative defect centers are reduced due to efficient exciton localization by QDs [17][18][19][20][21].…”
Section: Tuning the Optical Absorption Of Inp Qds To The Near-irmentioning
confidence: 99%
“…23 shows that defects are also introduced into the wetting layer, so at low temperatures, carriers can also be lost by tunnelling to nearby defect states. 24 Mode-locking was observed in these devices with pulse widths reducing by a factor 29 from 8.4 ps at 250 K to 290 fs at 20 K, and this correlates with the temperature dependence of threshold of the same structures, as shown in Fig. 2.…”
mentioning
confidence: 61%
“…Although the proton doses here are similar to those used in Ref. 8, their proton energy was much higher at 2.4 MeV so the displacement rate in our experiments is probably much higher because we have chosen the proton energy to maximize the atomic displacement rate in the dot layer itself.…”
Section: Effect Of Proton Bombardment On Inas Dots and Wetting Layer mentioning
confidence: 93%